1972
DOI: 10.4141/cjas72-073
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Colostrum and Milk Composition of Seven Breeds of Swine

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
15
3

Year Published

1977
1977
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 5 publications
5
15
3
Order By: Relevance
“…In contrast, however, Elsley et al (1969), Buitrago et al (197D, Frobish and Steel (1910) Miller et al (1971) and Fahmy (1972). The values for gross energy content are similar to those obtained by Fahmy (1912) and Siers et al (1976 Brooks and Davis (1969) and Elliott and Lodge (1911 For personal use only. Seerley et al (1974) and Elliott and Lodge (1917) …”
supporting
confidence: 78%
“…In contrast, however, Elsley et al (1969), Buitrago et al (197D, Frobish and Steel (1910) Miller et al (1971) and Fahmy (1972). The values for gross energy content are similar to those obtained by Fahmy (1912) and Siers et al (1976 Brooks and Davis (1969) and Elliott and Lodge (1911 For personal use only. Seerley et al (1974) and Elliott and Lodge (1917) …”
supporting
confidence: 78%
“…It was reported that sows from different breeds probably differ in the composition of their colostrum and milk (Fahmy 1972), yet very few studies have since been carried out to confirm this. The objectives of the present study were to establish whether there are differences in composition of colostrum and milk between sows from four genetic lines differing in body type and maternal abilities, and to determine if these are related to indices of metabolism in the circulation.…”
mentioning
confidence: 94%
“…This could have confounded results since O' Grady et al (1973) noted a great variation in milk protein content from one parity to the next, and Mahan (1998) also demonstrated an effect of parity on sow milk fat content. On the other hand, Fahmy (1972) noted that breeds that had higher levels of milk constituents generally lost more weight during lactation and had heavier litters at weaning. In the present study, the more maternal lines of sows (L and Y), which lost the most weight during lactation, also showed an advantage in terms of lactose content in colostrum.…”
mentioning
confidence: 99%
“…It is known that both the quantity of milk and its composition may limit the growth rate of the suckling piglet (Williams, 1995). Some differences in the nutrient composition of sow's milk according to breed have been reported (Fahmy, 1972;Zou et al, 1992), and therefore it may be that the IB sow would not be able to support the same sort of growth rates in her suckling piglets as the values observed in conventional or lean genotypes, due to a shortage in the provision of nutrients to the litter. Nevertheless, the hypothesis that the IB piglet would have a low capacity for body weight (BW) gain due to limitations in the metabolic use of nutrients or a limited protein accretion capacity cannot be ignored.…”
Section: Introductionmentioning
confidence: 99%